Kunst, køn og nekropolitik - Mikkel Krause Frantzen (The Royal Danish Library, 2015)
The concept of necropolitics, launched by Achille Mbembe in 2003, has had an increasing influence within various disciplines but not within arts, aesthetics and cultural studies. This is the point of departure for my article, which simply wants to address the following questions: